Akses Layanan Publik untuk Kawasan dan Transportasi Desa di Situgede Kota Bogor (ALPUKAT DESA) - Ilham Januar Pratama; Dela Watic Suyatno; Nurcahyo Ramadhan; Salma Tri Ambarsari; Aprilia Viola Wulandari; Adinda Maharani Hidayat; Muhamad Mulya Azhar; Agief Julio Pratama; M. Iqbal Nurulhaq; Tri Budiarto; Widya Hasian Situmeang; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (Lembaga Pengembangan Kinerja Dosen, 2025)
Situ Gede Sub-district in Bogor City has the potential to develop tourism, yet still faces challenges in promoting tourist destinations and in operating administrative systems that have not adopted digital technology. To address these issues, a mixed-method approach was used by combining qualitative and quantitative methods through interviews and questionnaires involving local residents and village officials. The results showed that the majority of respondents gave positive responses to digital innovation and expressed their willingness to use an online platform. As a result, a village website was developed to serve as a digital platform facilitating the management of population documents and tourism information. The website is designed to improve the effectiveness of public services and strengthen the promotion of the village’s potential. This digital solution serves as an innovative approach to deliver fast, accessible, and community-oriented public services by leveraging technology.